The Effectiveness of Grade C Coconut Shell Liquid Smoke Insecticide and Broflanilide Active Ingredient Insecticide Against Plutella xylostella L. (Lepidoptera: Plutellidae) on Cabbage Plants - Bilqis, Zanjabila Anida; Ikawati, Silvi (University of Brawijaya, 2025)
This research aims to find out the effectiveness of the coconut shell liquid smoke grade c and the insecticide active ingredient broflanilide to decreased larvae eating activity, larvae mortality, the percentage of larvae transformation into pupae and imago Plutella xylostella L., as an approach that can be used in controlling P. xylostella. The research was conducted at the Laboratory of Plant Pests and Diseases Department, Faculty of Agriculture, Universitas Brawijaya. Treatment consists of controls, Liquid smoke grade c 6%, Liquid smoke grade c 9%, Liquid smoke grade c 6% + Broflanilide 0.025 ml, Brofranilide 0,025 ml and Brofnanilide 0.05 ml, with repeated 4 times and each treatment used 20 P. xyostella larvae. The data obtained were analyzed ANOVA and DMRT with a 5% error level. The data larvae mortality of 1 hour after treatment and transformation larvae into imago were analyzed using Kruskal Wallis. According to the results of the study, there are 3 compound with the highest percentage that potential in controlling P. xylostella namely phenol, guaiacol, and syringol. The treatment that showed the best results on larvae mortality was found in the treatment of the mixture of Liquid Smoke grade c 6% + Broflanilide 0.025ml (81.21%) and broflanilide 0.05 ml treatment (86.85%). The mixture treatment decrease in eating activity up to 78.51%, the mixed treatment had an 16.25% in the percentage of larva transformation into pupae and 13.75% in the percentage transformation of the larva into imago.